Permafrost long term observatories of the Alfred-Wegener-Institute - Lange, Stephan; Grünberg, Inge; Bornemann, Niko; Lehr, Christian; Cable, William; Boike, Julia (Zenodo, 2021)
This document gives an overview of the data quality flagging routines used in the data-publications of the permafrost long term observatories of the Alfred-Wegener-Institute. To get the code, use the Subject links to github.